Advanced nanostructured materials : wide-band-gap oxides based magnetic semiconductors - Xing, Guozhong (2012)
Nanomaterials and Spintronics are focuses of research over the past ten years. The conjunction of electron spin with the charge manipulation in the semiconductor could lead to a whole new era in information technology, called semiconductor spintronics. It represents a new paradigm of accomplishing the functionalities of logic operation and data storage with high speed and low power consumption in next-generations of integrated magnetic sensors, transistors and lasers. The field of ferromagnetic semiconductors is dominated by Japan, rapidly advanced in United States and highlighted as an important emerging technology across continental Europe. Until recently, Singapore research groups have played a minor role in the field of ferromagnetic semiconductors. Semiconductor spintronics has already become a major research area. Spintronics is very likely to have a significant impact on future generations of devices.Operation of spintronic devices could consume much less energy because aligning spins is more efficient than redistributing charges. The discovery of ferromagnetic ordering in wide-band-gap semiconductors generated tremendous attention by the theoretical prediction that Mn doped p-type ZnO would show room temperature ferromagnetism (RTFM). Interestingly, over the past years, it has been well recognized that the major obstacle in studying the magnetism in dilute doped oxides is related to extrinsic tendency of metal clustering. The resulting attractive force between the magnetic cations leads to their aggregation, invalidating the main promise of diluted magnetic semiconductors (DMSs) and diluted magnetic oxides (DMOs) especially. Accordingly, initiating from the d0 magnetism observation addressed in 2005 by J. M. D. Coey et al. in undoped oxide systems, the demanding properties investigation of both DMSs and DMOs are emergent. Typically, as the extensively studied systems, wide-band-gap-oxides, e.g. ZnO and In2O3-based DMOs show Curie temperature (Tc) well above room temperature, and promising magneto-optical and magnetotransport characteristics. Steady progress is being made on this front, but recent reports demonstrate that progress is far from dormant. This is very demanding, because they have vital impact on the fundamental research development and practical application of DMOs.